Component characterization and commissioning of a gamma-PET prototype detector system - Binder, T. M.; Anagnostatou, V.; Dedes, G.; Kamada, K.; Kang, H. G.; Lovatti, G.; Nitta, M.; Safari, M.J.; Zoglauer, A.; Parodi, K.; Yamaya, T.; Thirolf, P.G. (Frontiers in Physics, 2022)
Hybrid imaging systems, comprising PET and Compton camera modules, have recently gained in interest, due to their capability to simultaneously detect positron annihilation photons and gamma-rays from single-photon emitting sources as also used in SPECT. A unique feature of such systems, however, is the capability to also be operated in a so called gamma-PET mode. Here, specific beta+- emitting radioisotopes (such as 44Sc, 10C or 14O) are used to detect triple-coincidences between two annihilation gamma-rays (in PET imaging) and a third, prompt photon (in Compton imaging), that is emitted by the deexcitation of the decay’s daughter nucleus. Consequently, an intersection between the line-of-response (LOR) and the Compton cone can be determined, which (in principle) allows to localize the photons’ emission vertices on a single decay basis. In practice, however, a few tens of events are required to localize a point source, which still results in a considerable sensitivity improvement compared to conventional PET imaging. For a proof-of-principle study, we used a pixelated GAGG crystal array (16 x 16 crystals; 1.45 x 1.45 x 6 mm3 crystal volume; 25 micron SPAD SiPMs as readout) as Compton camera scatterer and PET detectors, and a three-layered LYSO crystal array (1.2 x 1.2 x 6.66 mm3 crystal volume; 50 micron SPAD SiPMs as readout) as Compton camera absorber. We characterized the individual detector components with regard to their energy resolution and the capability to identify the various scintillator array’s individual crystals. Our first gamma-PET prototype was tested in PET-only and Compton-only imaging mode, in which spatial resolutions of 3.2-3.5 mm FWHM (PET-only mode) and 14.4 – 19.3 mm FWHM (Compton-only mode at 1274 keV) were achieved, respectively, using a 22Na point source and 10 iterations of an ML-EM reconstruction algorithm. By using triple-coincidences in a gamma-PET mode (event-wise intersection of the LOR and the Compton cone), we could demonstrate the capability of the prototype to perform a full 3D point source reconstruction and a good spatial resolution using only 77 events.